2014
DOI: 10.1080/17437199.2014.941722
|View full text |Cite
|
Sign up to set email alerts
|

Theories of behaviour and behaviour change across the social and behavioural sciences: a scoping review

Abstract: Interventions to change health-related behaviours typically have modest effects and may be more effective if grounded in appropriate theory. Most theories applied to public health interventions tend to emphasise individual capabilities and motivation, with limited reference to context and social factors. Intervention effectiveness may be increased by drawing on a wider range of theories incorporating social, cultural and economic factors that influence behaviour. The primary aim of this paper is to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
795
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 1,010 publications
(898 citation statements)
references
References 75 publications
9
795
0
17
Order By: Relevance
“…23 This is illustrated in a recent review of theories of behaviour change which found that only 3 out of 83 theories were integrative and set out to be comprehensive. 62,63 Models such as the Theory of Planned Behaviour 64 present a cognitive model of behaviour (attitudes, perceived norms and perceived behavioural control predict intentions which, in turn, predict behaviour), downplaying impulsive factors in decision-making, which may influence motivation (an important influence on behaviour). Beyond identifying potential influences on behaviour, the BCW also provides structured guidance for determining the content and format of interventions.…”
Section: The Utility Of the Behaviour Change Wheelmentioning
confidence: 99%
“…23 This is illustrated in a recent review of theories of behaviour change which found that only 3 out of 83 theories were integrative and set out to be comprehensive. 62,63 Models such as the Theory of Planned Behaviour 64 present a cognitive model of behaviour (attitudes, perceived norms and perceived behavioural control predict intentions which, in turn, predict behaviour), downplaying impulsive factors in decision-making, which may influence motivation (an important influence on behaviour). Beyond identifying potential influences on behaviour, the BCW also provides structured guidance for determining the content and format of interventions.…”
Section: The Utility Of the Behaviour Change Wheelmentioning
confidence: 99%
“…A definition of theory from a multidisciplinary consensus exercise is: 'a set of concepts and/or statements with specification of how phenomena relate to each other', providing 'an organising description of a system that accounts for what is known, and explains and predicts phenomena' ( [61], p. 5).…”
Section: Behaviour Change Theory: Specifying the Mechanisms Of Actionmentioning
confidence: 99%
“…These vary in complexity and range of application and many overlap with each other. A review led by psychologists, sociologists, anthropologists and economists identified 83 theories of behaviour and behaviour change, containing more than 1700 theoretical constructs [61,62]. Given this abundance of theories, researchers and intervention designers are faced with difficult decisions as to which theory or theories they should draw on [63].…”
Section: Behaviour Change Theory: Specifying the Mechanisms Of Actionmentioning
confidence: 99%
“…Despite these advances and calls-to-action, there remains a lack of specificity about interventions [30,34,35]. Although the CONSORT guidelines [36] for publishing the results of clinical trials call for describing the interventions studied, the historical roots for describing interventions are in a medical clinical trials model; describing complex behavioral interventions is quite different.…”
Section: Deconstructing Interventions or Unpacking The "Black Box"mentioning
confidence: 99%